Hubungan Efikasi Diri dengan Kontrol Gula Darah Pada Pasien Diabetes Melitus Tipe-2 di Puskesmas Gamping 2 Sleman Yogyakarta - Johan Ady Pranata; Ike Wuri Winahyu Sari (FORIKES, 2021)
Self-efficacy is considered to be a determinant of success in the self-care of people with type 2 diabetes mellitus. Currently, the prevalence of type 2 diabetes mellitus in Yogyakarta is the third highest in Indonesia, and the research on the correlation between self-efficacy and glycemic control is lacking. This study aimed to identify the correlation between self-efficacy and glycemic control in patients with diabetes mellitus at Gamping 2 Health Center Sleman Yogyakarta. This study was a descriptive correlational study using a cross-sectional approach with 47 respondents selected using a purposive sampling technique. The questionnaire used in this study was the Diabetes Management Self-Efficacy Scale (DMSES). The glycemic control measured using the value of Fasting Blood Sugar (FBS) in the last 3 months. The result of this study analyzed using the Spearman rank correlation test. There was a correlation between self-efficacy and glycemic control in patients with type 2 diabetes mellitus at Gamping 2 Health Center Sleman Yogyakarta with a p-value